Risk factors for hospitalization and pneumonia development of pediatric patients with seasonal influenza during February–April 2023 - Zhang, Yuqian; Huang, Xing; Zhang, Jianguo; Tao, Zhimin (Frontiers in Public Health, 2024)
Objectives In China influenza remains a low activity for continuous 3 years due to COVID-19 controls. We here sought to study the clinical characteristics and risk factors of the influenza infection among children after the mandatory COVID-19 restrictions were lifted. Methods We included 1,006 pediatric patients with influenza A virus (IAV) infection, enrolled in one tertiary hospital in Zhenjiang, Jiangsu Province, China, during February to April 2023. Patients were divided into the outpatient (n = 798) and inpatient (n = 208) groups, and their baseline characteristics were compared between two groups to conclude the risk factors for pediatric hospitalization. Separately, pediatric inpatients (n = 208) were further divided into the pneumonia and non-pneumonia groups with comparison of their clinical characteristics, including their laboratory test results and representative radiological features, to derive the key determinants for pneumonia development after hospitalization. Results Compared to outpatients, IAV-infected pediatric inpatients exhibited younger age, higher female: male ratio, more co-infection of influenza B virus (IBV) and hematological abnormality. Multivariate regression analysis determined the independent risk factors of hospitalization to be the clinical symptom of abdominal pain (OR = 2.63, [95% CI, 1.05–6.57], p = 0.039), co-infection of IBV (OR = 44.33, [95% CI, 25.10–78.30], p = 0.001), elevated levels of lymphocytes (OR = 2.24, [95% CI,1.65–3.05], p = 0.001) and c-reactive proteins (CRPs) (OR = 1.06, [95% CI, 1.03–1.08], p = 0.001) upon hospital admission. Furthermore, the cough symptom (OR = 17.39, [95% CI, 3.51–86.13], p = 0.001) and hospitalization length (OR = 1.36, [95% CI, 1.12–1.67], p = 0.002) were determined to be risk factors of pneumonia acquirement for pediatric inpatients. Conclusion While the abdominal pain, viral co-infection and some hematological abnormality mainly contribute to hospitalization of pediatric patients with IAV infection, the length of hospital stay and clinical sign of coughing upon hospital admission constitute the key determinants for nosocomial pneumonia development.